STYLISTIC DEVICES IN ENGLISH AND UZBEK LANGUAGES:A COMPARATIVE ANALES - Allayev Zafar Mengboyivich, Umbarova Jasmina Muxidden kizi (International Journal of Literature and Language Studies, 2026)
This article examines stylistic devices in English and Uzbek languages from a comparative perspective. The aim of the study is to identify common and distinctive features of figurative means in both languages and to analyze their functional characteristics in literary and scientific texts. The article compares metaphor, metonymy, epithet, simile, alliteration, anaphora, and other stylistic figures based on English and Uzbek language materials.